Notes on Early Land Plants Today. 30. Transfer of some taxa from Anastrophyllum (Anastrophyllaceae, Marchantiophyta) - Váňa, Jiří; Söderström, Lars; Hagborg, Anders; Konrat, Matt Von (Phytotaxa, 2013)
The genus Anastrophyllum Stephani (1893: 139) was treated in a broad sense by e.g. Schuster (1969) and has usually been so until recently. De Roo et al. (2007) showed that the genus is polyphyletic and removed Sphenolobus (Lindberg 1874: 369) Berggren (1898: 22) and Crossocalyx Meylan (1939: 266). Subsequently Váňa & Engel (2013) removed subgenus Zantenia Hattori (1966: 342). However, two other elements remain, that also deserve to be removed.